Pefloxacin and its derivative, novel inhibitors of the SARS-CoV-2 Main protease (3CLpro) and their pharmacokinetics prediction: An in silico analysis - Adediran, Emmanuel Oluwaseun (Archives of Pharmacy and Pharmaceutical Sciences, 2022)
For over two years, COVID-19 pandemic has been a major global health concern and threat to human life. In the SARS-CoV2 macromolecules, the 3-chymotrypsin like protease (3CLpro or main protease) has been identified to be crucial and essential for viral survival, processing of the viral polyproteins and has been explored as a target in COVID-19 drug discovery. Although vaccines and other various inhibitors have been designed and launched, the emergence of the variant of this virus has put an unrelenting effort of researchers to this end. Also, the high cost of manufacturing these molecules coupled with the occurrence of drug resistance is a concern. Herein, Pefloxacin and its derivative for the first time were screened for their inhibitory activity against the SARS-CoV2 main protease through in silico analysis and their pharmacokinetic properties were evaluated. Interestingly, from the docking results, they both bind with high affinity at the active site of the protein. Moreover, they showed excellent pharmacokinetic and drug - likeness properties. Derivatization of Pefloxacin at the C7 position prevents its blood-brain barrier permeability. Overall, the dual antibacterial and potential antiviral activities of these two molecules make them promising drug candidates for COVID-19 management.